2014
DOI: 10.1530/joe-14-0486
|View full text |Cite
|
Sign up to set email alerts
|

Bone quality is affected by food restriction and by nutrition-induced catch-up growth

Abstract: Growth stunting constitutes the most common effect of malnutrition. When the primary cause of malnutrition is resolved, catch-up (CU) growth usually occurs. In this study, we have explored the effect of food restriction (RES) and refeeding on bone structure and mechanical properties. Sprague-Dawley male rats aged 24 days were subjected to 10 days of 40% RES, followed by refeeding for 1 (CU) or 26 days long-term CU (LTCU). The rats fed ad libitum served as controls. The growth plates were measured, osteoclasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 41 publications
(47 reference statements)
4
38
0
1
Order By: Relevance
“…Supplemented heifers had higher plasma concentrations of insulin, IGF-1 and T3 hormone as well as thicker PZ and HZ and larger terminal hypertrophic chondrocytes (Table 5-7 and Table 5-8). Similarly, Pando et al (2014) reported severe reductions in the concentration of circulating IGF-1 (reduced to about 20% of concentration in control animals) during caloric restrictions associated with a smaller epiphyseal growth plate. Moreover, IGF-1 null mice have a smaller HZ and terminal hypertrophic chondrocytes as well as slower bone elongation rate when compared to wild-type mice.…”
Section: Longitudinal Growth and Hormones Concentrationmentioning
confidence: 80%
See 4 more Smart Citations
“…Supplemented heifers had higher plasma concentrations of insulin, IGF-1 and T3 hormone as well as thicker PZ and HZ and larger terminal hypertrophic chondrocytes (Table 5-7 and Table 5-8). Similarly, Pando et al (2014) reported severe reductions in the concentration of circulating IGF-1 (reduced to about 20% of concentration in control animals) during caloric restrictions associated with a smaller epiphyseal growth plate. Moreover, IGF-1 null mice have a smaller HZ and terminal hypertrophic chondrocytes as well as slower bone elongation rate when compared to wild-type mice.…”
Section: Longitudinal Growth and Hormones Concentrationmentioning
confidence: 80%
“…In addition, the percentage change in bone volume (BV/TV; Figure 4-25) during Phase 1 also indicated that the loss of trabecular bone volume was slightly reduced in steers fed high CP during ME restriction. Pando et al (2014) have demonstrated that after only one day of re-alimentation there was a significant increase in collagen fibre deposition in the trabecular bone of rats, and this was accompanied by a rise in BAP and IGF-1 to the same concentration as rats in the control group. This shows that bone formation is a very dynamic process and highly responsive to nutrition and a change in nutrition.…”
Section: Trabecular Bone Structurementioning
confidence: 92%
See 3 more Smart Citations